Answer:
option B
Step-by-step explanation:
We have three different function for h(x)
![h(x)= \frac{1}{4}x-4, x](https://tex.z-dn.net/?f=h%28x%29%3D%20%5Cfrac%7B1%7D%7B4%7Dx-4%2C%20x%3C%3D0)
WE have x<=0, so the graph starts at x=0 and goes down
Plug in 0 for x
![h(0)= \frac{1}{4}(0)-4](https://tex.z-dn.net/?f=h%280%29%3D%20%5Cfrac%7B1%7D%7B4%7D%280%29-4)
So h(0)= -4
When x=0, y= -4
The graph starts at (0,-4) and goes down
![h(x)= \frac{1}{3}x-3, 0](https://tex.z-dn.net/?f=h%28x%29%3D%20%5Cfrac%7B1%7D%7B3%7Dx-3%2C%200%3Cx%3C%3D3)
x lies between 0 and 3, so the graph starts at x=0 and ends at x=3
Plug in 0 for x
![h(0)= \frac{1}{3}(0)-3](https://tex.z-dn.net/?f=h%280%29%3D%20%5Cfrac%7B1%7D%7B3%7D%280%29-3)
So h(0)= -3
When x=0, y= -4
Plug in 3 for x
![h(3)= \frac{1}{3}(3)-3=-2](https://tex.z-dn.net/?f=h%283%29%3D%20%5Cfrac%7B1%7D%7B3%7D%283%29-3%3D-2)
When x=3, y= -2
The graph starts at (0,-4) and ends at (3, -2)
![h(x)= \frac{1}{2}x-2, x>=4](https://tex.z-dn.net/?f=h%28x%29%3D%20%5Cfrac%7B1%7D%7B2%7Dx-2%2C%20x%3E%3D4)
WE have x>=4, so the graph starts at x=4 and goes to the right
Plug in 4 for x
![h(4)= \frac{1}{2}(4)-2](https://tex.z-dn.net/?f=h%284%29%3D%20%5Cfrac%7B1%7D%7B2%7D%284%29-2)
So h(4)= 0
When x=4, y= 0
The graph starts at (4,0) and goes to the right.
SEcond graph is correct